RANCANGAN KUNCI PINTU OTOMATIS MENGGUNAKAN RFID BERBASIS MIKROKONTROLER DI ASRAMA BRAVO 1, 2, 3 CURUG 1 SEKOLAH TINGGI PENERBANGAN INDONESIA - Reinhard Ferry Wijaksana; KGS. M. Ismail; Oka Fatra (Langit Biru: Jurnal Ilmiah Aviasi, 2019)
The key holds the role in the security system. Most of the door lock system still using a mechanic conventional key. The development of technology gives the solution in a key system as a better security system. So, it is needed to use and to optimize the tools that could give best security level in door lock system including convenience and comfort in case of use. one of that security system is using RFID that developed as automatic door lock system. The purpose of this research is to use based on micro controller Arduino nano ATmega 328p and the location at the dormitory door Bravo 1,2,3 to install an automatic door lock tool. Which consists of a mantle of door security that solenoid as an automatic security lock. Identification device consists of RFID Reader and RFID card. Lamp indicator using Light Emitting Diode (LED). When RFID reader reads RFID card, then the LED lamp will turn on and solenoid door lock works and if RFID card is not read in accordance with the microcontroller, LED and solenoid door lock wouldn’t work. With this method it is expected to work as desired